2015
DOI: 10.1097/sla.0000000000000934
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Compliance With an Antibiotic Prophylaxis Guideline to Prevent Pediatric Surgical Site Infection

Abstract: A multifaceted intervention improved compliance with a pediatric AP guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 31 publications
3
39
0
3
Order By: Relevance
“…In cases with post‐surgical devices such as chest drains, urinary catheters and implants, we found evidence of guideline‐non‐adherent extended post‐procedural SAP use, in some cases for up to 4 days. This has been noted in other studies despite a lack of evidence supporting this practice and recommendations to the contrary . There may be an exaggerated perception of SSI risk associated with devices and benefits of ongoing prophylaxis, leading to the overuse of antimicrobials.…”
Section: Discussionmentioning
confidence: 90%
“…In cases with post‐surgical devices such as chest drains, urinary catheters and implants, we found evidence of guideline‐non‐adherent extended post‐procedural SAP use, in some cases for up to 4 days. This has been noted in other studies despite a lack of evidence supporting this practice and recommendations to the contrary . There may be an exaggerated perception of SSI risk associated with devices and benefits of ongoing prophylaxis, leading to the overuse of antimicrobials.…”
Section: Discussionmentioning
confidence: 90%
“…Other reports in the medical literature describe interventions to increase compliance with recommended perioperative antibiotic prescribing practices, but these other reports mostly focus on the timing of the initial dose of PPA. 10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28] A limited number of reports focus on ensuring appropriate PPA redosing in prolonged surgeries 1 ; those that do document only modest improvements in the redosing rate. 12,13 We demonstrated that our multidisciplinary and multifaceted approach was effective at producing immediate and sustained improvements in guideline compliance, and the magnitude of benefit was much greater than in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Effective interventions are often multifaceted and have included interdisciplinary guideline development, prescriber feedback, educational initiatives, posters, checklists, and forced functions. [36][37][38][39][40][41] In the acute surgical setting, Weiser and colleagues 42 showed that the use of a surgical checklist is feasible, effectively improves adherence to antibiotic prophylaxis guidelines and reduces surgery-associated complications and mortality. A 3-phase surgical safety checklist (surgical briefing, surgical time out and surgical debriefing) has recently been implemented at our institution and may address some of these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Despite interventions and the use of surgical checklists, full adherence to antibiotic guidelines in the operating room continues to be suboptimal. [6][7][8] As the population ages, older adults make up an increasing proportion of patients admitted to hospitals, and antibiotics play an important role in the management of many diseases. This is especially true of older patients who are admitted to acute care general surgery services, where antibiotics are routinely used for both treatment and prophylactic purposes.…”
mentioning
confidence: 99%